Structural features of cross‐sectional wing bones in the griffon vulture (Gyps fulvus) as a prediction of flight style. (5th November 2018) - Frongia, Gian N.; Muzzeddu, Marco; Mereu, Paolo; Leoni, Giovanni; Berlinguer, Fiammetta; Zedda, Marco; Farina, Vittorio; Satta, Valentina; Di Stefano, Marco; Naitana, Salvatore
Abstract: Flight is an energetically costly form of transport imparting biomechanical stress that acts upon the wing bones. Previous studies have suggested that the cross‐sectional and microstructural features of wing bones may be adapted to resist biomechanical loads. During flight, however, each wing bone potentially experiences a unique loading regime. To assess possible differences among wing bones, we analyzed the microstructural features of the humerus, radius, ulna, and carpometacarpus (CMC) in eight griffon vultures ( Gyps fulvus ). Vascular canal orientation was evaluated in the diaphysis of the wing bones. Laminarity index (LI) was significantly different in the humerus versus CMC and ulna versus CMC. Results showed a lower proportion of circular vascular canals, due to resistance to torsional loads, in CMC than in humerus and ulna. The midshaft cross‐section revealed an elliptical shape in the CMC compared to the circular shape observed in the other wing bones, with a maximum second moment of inertia ( I max ) orientation which suggests a capacity to withstand bending loads in a dorsoventral direction. The volumetric bone mineral density in the diaphysis was statistically different in CMC compared to the other bones analyzed. Its lower mineral density may reflect an adaptation to a different type and load of stresses in CMC compared to the proximal wing bones. No significant difference was found in the relative cortical area (CA/TA) among the four elements, while the polar moment of area J (Length‐standardized) revealed a higher resistance to torsional load in the humerus than in the other bones. Our results would seem to indicate that griffon wing bones are structured as an adaptation, represented by two segments that respond to force in two ways: the proximal segment is specially adapted to resist torsional loads, whereas the distal one is adapted to resist bending loads. Abstract : Examples of vascular canals in a CMC section of griffon vulture: the canals can have longitudinal (L), circular (C), radial (R) or oblique (O) orientations.